Development of the Alpha female character through habits based on Islamic education perspective - Ayu Fitria Nur Utami; Yusup Rohmadi (UIN Raden Mas Said Surakarta, 2021)
When women reach adolescence, they undergo psychological changes that affect their identity; thus, a woman must be able to instill positive values in order to develop a strong sense of self-worth. A woman with an Alpha female figure is depicted in the picture. This study aims to explain the figure of the Alpha female in Islamic female characters, as well as to examine the steps for a Muslim teenager to grow as such an Alpha female through habits. The paper analysis method was used in this study, and the documents used by the researcher were research materials from Henry's book; The Girl Guide, and Felix y Siauw’s; How to Master your Habits. A descriptive qualitative analysis was used to analyze the data. The results of the study indicate that developing the Alpha female through habits in the context of Islamic education can be accomplished by first, providing motivation to improve. Second, training and repetition of activities related to alpha female creation, such as alpha friend, alpha student, professional alpha, and alpha look. The Alpha Female required a third time and consistency to evolve. The fourth is to be an expert, namely being able to form habits, control habits, and dominate habits. The results of this study contribute to the material for a woman in an effort for better self-development.